Influence of entrepreneurial team knowledge conflict on ambidextrous entrepreneurial learning: A dual-path perspective of entrepreneurial resilience and fear of failure - Xianyue Liu; Yuan Yuan; Rui Sun; Chenxi Zhao; Dali Zhao (Journal of Innovation & Knowledge (JIK), 2023)
Entrepreneurial activity is a continuous learning process that is rife with uncertainty, and the dialectical interactions arising from knowledge differences and knowledge conflict among individuals on an entrepreneurial team influence team members' entrepreneurial learning. By reference to fear of failure and entrepreneurial resilience, this study investigates the dual paths by which entrepreneurial team knowledge conflict influences ambidextrous learning to clarify the two sides of entrepreneurial team knowledge conflict and to explore the positive influence of fear of failure in this context. The results of empirical tests of a sample of 238 entrepreneurial teams show that (1) entrepreneurial team knowledge conflict positively influences ambidextrous learning; (2) fear of failure plays a significant mediating role in the relationship between entrepreneurial team knowledge conflict and exploratory learning, although its mediating role in the relationship between entrepreneurial team knowledge conflict and exploitative learning is not significant; and (3) entrepreneurial resilience plays a significant mediating role in the relationships between entrepreneurial team knowledge conflict and exploitative learning and between entrepreneurial team knowledge conflict and exploratory learning. The findings of this research explain the mechanism by which entrepreneurial team knowledge conflict affects entrepreneurial learning, expand the field of application of knowledge conflict, enrich the research on knowledge conflict, and provide practical insights that can allow entrepreneurial teams to manage knowledge conflict, eliminate fear of failure, and promote entrepreneurial learning.
Keywords: M130; 650; Ambidextrous entrepreneurial learning; Fear of failure; Knowledge conflict; Organizational resilience